2022
DOI: 10.1007/s11657-022-01105-w
|View full text |Cite
|
Sign up to set email alerts
|

An 11-year longitudinal analysis of refracture rates and public hospital service utilisation in Australia’s most populous state

Abstract: Summary This detailed 11-year longitudinal analysis calculated the public health cost of managing refractures in people aged ≥ 50 years in Australia’s most populous state. It provides current and projected statewide health system costs associated with managing osteoporosis and provides a foundation to evaluate a novel statewide model of fracture prevention. Purpose The purpose of this longitudinal analysis was to calculate current and projected ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It Also suggests that as time increases and time between 1 st and fracture prolongs then frequency of subsequent fracture decreases [20] Our study revealed that the hazard ratio for re fracture was not statistically significant with gender and that difference was less significant than that in first fracture [21] while death due to fracture for higher in man than woman. [22,23,24]…”
Section: Discussionmentioning
confidence: 99%
“…It Also suggests that as time increases and time between 1 st and fracture prolongs then frequency of subsequent fracture decreases [20] Our study revealed that the hazard ratio for re fracture was not statistically significant with gender and that difference was less significant than that in first fracture [21] while death due to fracture for higher in man than woman. [22,23,24]…”
Section: Discussionmentioning
confidence: 99%
“…This undertreatment carries enormous costs: to individuals, through preventable fracture-related morbidity [ 8 10 ] and mortality [ 11 , 12 ], and to society, through healthcare expenditure [ 13 15 ] and loss of productivity [ 5 ]. Moreover, all these metrics are expected to worsen with an ageing population [ 16 ]. To address the osteoporosis treatment gap, coordinated secondary fracture prevention services termed fracture liaison services (FLS) have been implemented at more than 800 sites across 54 countries [ 17 ].…”
Section: Introductionmentioning
confidence: 99%